SOSIALISASI PEMANFAATAN EKSTRAK UBI JALAR UNGU DAN BUNGA TEROMPET UNGU SEBAGAI INDIKATOR ALAMI UNTUK MENDETEKSI BORAKS DAN FORMALIN PADA MAKANAN - Dyah Fitriani; Bambang Trihadi; Eni Widiyati (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Borax and formalin are chemicals that are often used as desfinfectants, corpse preservatives, cosmetics and so on. The misused use of borax and formalin can be detrimental to human life. Misuse of these two chemicals is often found in food. If borax and formalin enter the body it can cause nausea, vomiting, diarrhea, cancer and even death. The need to detect borax and formalin in food quickly and easily, so that the public can avoid the consumption of foods that contain these harmful ingredients. The purpose of this community service activity is to provide knowledge and training to the community, especially housewives who are members of the Muslimah (Salimah) subdistrict of Bengkulu City to be able to detect borax and formalin on food using natural indicators, namely purple trumpet flowers and purple sweet potatoes. The results of this activity show that 90% of partners can understand